Effect of the Quranic Verses Recitation on Depressive Symptoms among Cancer Patients at Tertiary Care Hospital, Karachi - Ahmed, Farhan; Nazly, Afshan; Amarsi, Yasmin Noorali; Bashir, Shahzad (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To assess the effectiveness of recitation of the Quranic verses on depressive symptoms among cancer patients. METHODOLOGY: This Pre-Post quasi-experimental single-group study was conducted from December 2021 to January 2022 in the Oncology department at Dr. Ziauddin Hospital Karachi. A total of 50 depressed Cancer patients participated in the study. Participants were recruited through the Consecutive sampling technique, which included being Muslim, having a one-month hospital stay, and a diagnosis of depression. Participants were assessed through the Hamilton Depression Scale (HAM-D). Data was analyzed through frequency and proportions for variables, and median and interquartile range differences were compared using the Wilcoxon signed-rank test. The association of depression was checked by Spearman rank correlation. RESULTS: Out of 50 participants, 32(64%) were males, and 18(36%) were females; 46(92%) were married; 50(100%) participants were belongs to Muslim religion and had a length of stay for 1 to 3 months durations. The comparison of HAM-D total scores revealed a median of 20.5 (IQR= 21-20) in the pre-test, which decreased to 13 (IQR= 14-12) in the post-test after one month of intervention. This reduction was statistically significant (p<0.05). CONCLUSION: The Quranic verses recitation is an effective and safe therapy for reducing depressive symptoms among cancer patients. The depression score significantly reduced after this intervention.